Digital Wallet Usage by the 2019 Class of Students at the Faculty of Islamic Business and Economics of IAID Ciamis (DANA Application Case Study) - Maulani, Gita Resta; Ramdani, Eggy Armand; Fani, Andifa Dwi (Syari'ah Economics, 2023)
This study aims to determine how consumer perceptions relate to the features of using Dana digital wallets, to determine how consumer perceptions relate to the security of using Dana digital wallets, to determine how consumer perceptions relate to the ease of use of Dana digital wallets. This research uses qualitative methods through interviews and documentation. Informants in this study are people who have knowledge about the topic under study. As well as data analysis using analytical techniques in the form of data reduction, data presentation and drawing conclusions. Based on the results of this study, it has been concluded that: First, consumer satisfaction with the use of DANA application is generally positive because the use of DANA application as a digital wallet service in transactions can make it easier for consumers and the use of digital wallets is also more efficient than cash. Second, the factor of consumer satisfaction with the use of the DANA application is the security that guarantees all transactions and user data. Third, based on the research conducted, it can be concluded that consumer satisfaction with the use of the DANA application is the convenience in using the DANA digital wallet application.